An Enzybiotic Cocktail Effectively Disrupts Preformed Dual Biofilm of Staphylococcus aureus and Enterococcus faecalis - Salim Manoharadas; Naushad Ahmad; Mohammad Altaf; Abdulwahed Fahad Alrefaei; Basel F. Al-Rayes (MDPI AG, 2023)
Multidrug-resistant bacterial infections are on the rise around the world. Chronic infections caused by these pathogens through biofilm mediation often complicate the situation. In natural settings, biofilms are often formed with different species of bacteria existing synergistically or antagonistically. Biofilms on diabetic foot ulcers are formed predominantly by two opportunistic pathogens, Staphylococcus aureus and Enterococcus faecalis. Bacteriophages and phage-based proteins, including endolysins, have been found to be active against biofilms. In this study, we evaluated the activity of two engineered enzybiotics either by themselves or as a combination against a dual biofilm formed by S. aureus and E. faecalis in an inert glass surface. An additive effect in rapidly disrupting the preformed dual biofilm was observed with the cocktail of proteins, in comparison with mono treatment. The cocktail-treated biofilms were dispersed by more than 90% within 3 h of treatment. Apart from biofilm disruption, bacterial cells embedded in the biofilm matrix were also effectively reduced by more than 90% within 3 h of treatment. This is the first instance where a cocktail of engineered enzybiotics has been effectively used to impede the structural integrity of a dual biofilm.